Locational, neighbourhood and physical characteristics of residential rental properties: A review - Sani, Adamu; Mohammed, Mohammed Ishaq; Usman, Hamza (Journal of Commerce, Management, and Tourism Studies, 2023)
The residential rental market plays a crucial role in housing provision, yet our understanding of its locational, neighborhood, and physical characteristics remains limited. This paper presents a comprehensive review of existing literature pertaining to these fundamental aspects of residential rental properties. By synthesizing findings from a wide range of academic studies and reports, we aim to shed light on the key factors that influence the rental property landscape. The study strategically explores the locational attributes that impact rental property preferences and values. This includes proximity to essential amenities such as schools, hospitals, public transportation, and commercial centers. Understanding how these locational factors influence rental demand and pricing patterns can provide valuable insights for both renters and landlords., Investigate the role of neighborhood characteristics in shaping rental markets. Neighborhood safety, accessibility to recreational areas, quality of public services, and social demographics are among the key factors that influence rental property selection. By analyzing these features, we identify potential correlations between neighborhood attributes and rental property performance., the study delves into the physical characteristics of residential rental properties. This aspect involves examining the features of the properties themselves, such as property size, layout, age, and amenities. Understanding how these physical attributes affect rental values and tenant satisfaction can help property owners optimize their investments and improve tenant retention. Moreover, in this study the review addresses the dynamic interplay between locational, neighborhood, and physical factors in shaping rental property markets. By recognizing the complex relationships between these variables, policymakers, real estate developers, and investors can devise informed strategies to create sustainable and inclusive rental housing solutions. The paper concludes with a call for further research in this field, emphasizing the need for empirical studies that capture changing rental market dynamics, especially in the context of evolving urban landscapes and housing preferences. Through this comprehensive review, we aim to contribute to a deeper understanding of locational, neighborhood, and physical characteristics in residential rental properties, thus enabling more effective and evidence-based decision-making within the rental housing sector.